2019
DOI: 10.1017/ice.2019.218
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of an electronic medical record (EMR)–driven intensive care unit (ICU)-antimicrobial stewardship (AMS) ward round: Assessing the “Five Moments of Antimicrobial Prescribing”

Abstract: Objective:The primary objective of this study was to examine the impact of an electronic medical record (EMR)–driven intensive care unit (ICU) antimicrobial stewardship (AMS) service on clinician compliance with face-to-face AMS recommendations. AMS recommendations were defined by an internally developed “5 Moments of Antimicrobial Prescribing” metric: (1) escalation, (2) de-escalation, (3) discontinuation, (4) switch, and (5) optimization. The secondary objectives included measuring the impact of this service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Indeed, ensuring discontinuation of unnecessary antibiotics remains the most common recommendation in AMS interventions. 42 Studies have shown that in the absence of the full team compliment or if decisions are not communicated to the pertinent role player, potential time delays can have an impact on patient outcomes. 43 Lack of standardisation has been noted in other surgical teams 19 44 45 where key aspects of care may be overlooked and is associated with suboptimal patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, ensuring discontinuation of unnecessary antibiotics remains the most common recommendation in AMS interventions. 42 Studies have shown that in the absence of the full team compliment or if decisions are not communicated to the pertinent role player, potential time delays can have an impact on patient outcomes. 43 Lack of standardisation has been noted in other surgical teams 19 44 45 where key aspects of care may be overlooked and is associated with suboptimal patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…46 49 In addition, inconsistent provision of clinical and infection-related information in the update can result in loss of valuable time, limiting the ability for generating relevant and correct information. 50 Despite the increasing threat of antibiotic resistance and HCAIs, it is interesting to note that few of the existing checklists, other than those designed for dedicated AMS rounds, 42 alert a surgical team to the key aspects of AMS and infection prevention and management. An opportunity exists to apply AMS and IPC principles to every single patient on every ward round and should not be reserved to dedicated stewardship rounds only.…”
Section: Discussionmentioning
confidence: 99%
“…The core activity of many Australian AMS programs are post-prescription ward rounds [1,12,32,33]. These multidisciplinary rounds comprised of an AMS pharmacist and an ID physician are a highly visible service in Australian hospitals with paper-based medication charts, enabling opportunity for impromptu discussions between clinicians and AMS teams about patients of concern.…”
Section: Limitations Of Emr For Ams In Australiamentioning
confidence: 99%
“…Local evidence for hospital AMS programs led by or including ID pharmacists has shown increased antimicrobial prescribing appropriateness, reduced use of target antimicrobials and provision of cost savings without adversely impacting clinical outcomes such as length of stay and mortality 22‐25 . Pharmacists are continuing to show their expertise in specific subspecialty areas within AMS, including antifungal stewardship, 26 and antimicrobial allergy de‐labelling 27,28 .…”
Section: Evidence Of Pharmacy Impact In Infectious Diseasesmentioning
confidence: 99%